Investigation and Application of Water-Saving Monitoring Technology in Public Institutions - WANG Kang; ZHENG Yongjie; ZHANG Zhen; TANG Yanping; SONG Wenhao; GUO Xiaoming (Renmin Zhujiang)
Considering the characteristics of water use and the current situation of water facilities in public institutions,this study comprehensively employs the Internet of Things (IoT),cloud deployment,databases,three-dimensional (3D) visualization,and other advanced techniques to create a water-saving reconstruction scheme with integrated software and hardware for public institutions.Therefore,a smart water management platform for public institutions is built to implement advanced water-saving concepts and improve the water management level.The main research results are as follows:① By intelligent remote monitoring equipment,the multiclass water measurement network is designed to realize the fine collection of zonal water use data;② this study designs a reconstruction scheme of water facilities and explores the utilization mode of unconventional water sources to improve the utilization efficiency of water resources;③ multiple algorithms and statistical methods are used to analyze the time series of water use data,and thus this study realizes the analysis of pipeline network leakage and damage,identification of water use anomalies,and water-saving statistical analysis,and the investigation of water use laws;④ the platform with functions of monitoring and early warning is established to achieve real-time remote monitoring of water use,statistical analysis of historical water use,and identification and warning of pipe network leakage,so as to detect water anomalies in time and save water.The research results are first applied to the construction of the water-saving institution of the Pearl River Water Resources Commission to build a benchmark for the construction of water-saving institutions in the southern region.On the basis of application experience,the comprehensively integrated monitoring technology for water-saving in public institutions is developed,which provides a new idea for public institutions to save water.